2020
DOI: 10.1186/s40734-020-0083-0
|View full text |Cite|
|
Sign up to set email alerts
|

Economic evaluation of AbobotulinumtoxinA vs OnabotulinumtoxinA in real-life clinical management of cervical dystonia

Abstract: Background: Botulinum neurotoxins type A (BoNT-As) are commonly used treatments for cervical dystonia (CD). Clinical trials have demonstrated the benefits of them in these patients, but data from real-life clinical practice as well as comparative data on the cost and outcome of different BoNT-A formulations are limited. The aim of this study was to compare abobotulinumtoxinA (aboBoNT-A) and onabotulinumtoxinA (onaBoNT-A) on their clinical outcomes and drug costs in real-life clinical practice. Methods: This an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A 2015 study, noting the effectiveness of BoNT-As for patients with CD, concluded that cost-effectiveness studies for these patients in the US were limited and that additional research was needed [ 26 ]. A 2020 article comparing cost-effectiveness of aboBoNT-A and onaBoNT-A in 356 adult patients with CD in Europe and Australia indicated that treatment with aboBoNT-A may be less costly and lead to improved clinical outcomes when compared with onaBoNT-A [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study, noting the effectiveness of BoNT-As for patients with CD, concluded that cost-effectiveness studies for these patients in the US were limited and that additional research was needed [ 26 ]. A 2020 article comparing cost-effectiveness of aboBoNT-A and onaBoNT-A in 356 adult patients with CD in Europe and Australia indicated that treatment with aboBoNT-A may be less costly and lead to improved clinical outcomes when compared with onaBoNT-A [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a study that suggests that the treatment for cervical dystonia with ABO may be less costly and lead to improved clinical outcomes when compared with ONA. There is another study that suggests that ABO may have more intense and lasting effects, but in all cases, the results are relativized because the calculations are made on the doses recommended by the FDA for each pathology and according to each formulation, which are, therefore, not comparable [ 27 , 28 ].…”
Section: Therapeutic Use For Botulinum Neurotoxinsmentioning
confidence: 99%
“…This causes repetitive rotating motion of the head, neck, and shoulder, as well as painful and disabling abnormal posture. [7,8] Another group of patients into whom we injected BoNT is chronic migraine patients. It is considered that nociceptive fibers inhibit peripheral sensitization and reduce central sensitization, except local muscle paralysis caused by BoNT in chronic migraine.…”
Section: Introductionmentioning
confidence: 99%